Besouros rola-bostas (Coleoptera: Scarabaeidae: Scarabaeinae) e suas funções ecológicas ao longo de um gradiente altitudinal tropical - Cassio Alencar Nunes (2015)
Mountains provide an interesting scenario to study biodiversity responses to macroclimate, as environmental conditions change rapidly due to elevation over short spatial distances. Generally, biodiversity decreases with increasing altitude, following geophysical and climatic trends. Although there is lot of data on how taxonomic diversity responds to altitude, there is a lack of information on what happens to other facets of biodiversity like functional and phylogenetic diversity. Studies that merged the multifaceted concept of diversity with the spatial partition are very rare. Our goal was to understand what happens to dung beetles community along a tropical altitudinal mountain gradient, including the spatial partition of taxonomic and functional diversities instead of using only richness and abundance as proxies of biodiversity. This study was performed along a mountain in the Espinhaços range, Southeast Brazil. The altitudinal gradient ranged from 800 up to 1400 m a.s.l. and we collected dung beetles every 100 m of altitude. We used the Rao quadratic entropy decomposition of diversity to calculate , and diversity for taxonomic and functional diversity of dung beetles. Further, climatic, soil and vegetation variables were used to explain variation on communitys attributes along the altitudinal gradient. Dung beetles richness declined with altitude and it is related to climatic and vegetation variables, but functional diversity did not follow the same pattern. Over 50% of taxonomic diversity is caused by among altitudes diversity (), but almost 100% of functional diversity is caused by component. Contrasting taxonomic with functional diversity suggest that there is ecological redundancy among communities and environmental variables are filtering species in terms of Grinnellian niche, but not in terms of Eltonian niche. taxonomic diversity is caused mainly by turnover components and it reinforces the idea that different environmental filters, provided by elevation, are selecting dung beetles species in terms of physiological niche. We think that in a global warming scenario, upslope range shifts, mountaintop and lowland extinctions will lead to even bigger loss of diversity than expected as taxonomic diversity among altitudes is high and proportioned mainly by turnover of species.